Keratinous biomarker of mercury exposure associated with amyotrophic lateral sclerosis risk in a nationwide U.S. study. Issue 5 (2nd July 2020) - Andrew, Angeline S.; O'Brien, Katie M.; Jackson, Brian P.; Sandler, Dale P.; Kaye, Wendy E.; Wagner, Laurie; Stommel, Elijah W.; Horton, D. Kevin; Mehta, Paul; Weinberg, Clarice R.
Abstract: Objective : The majority of cases of the fatal neurodegenerative disease amyotrophic lateral sclerosis (ALS) are of unknown etiology. A proportion of these cases are likely to be attributable to contaminant exposures, although the specific environmental etiology of ALS remains largely a mystery. Certain forms of the neurotoxic metal mercury readily cross into the central nervous system. Fish is a dietary source of methylmercury, but also of beneficial components, such as omega-3 polyunsaturated fatty acids. Prior work using clinic-based studies of toenails and hair as keratinous biomarkers of exposure suggest elevated mercury levels in ALS patients compared with controls. We sought to validate this relationship in a U.S. case-control comparison of mercury levels in nail clippings. Methods : We performed trace element analysis using inductively coupled plasma mass spectrometry (ICP-MS) on the nail clippings of n  = 70 female, geographically representative ALS patients from the National ALS Biorepository and compared them to n  = 210 age-matched controls from a set of n  = 1216 nationally distributed controls from the Sister and Two Sister Studies. Results : Compared to the lowest quartile of nail mercury, moderate levels were associated with decreased risk of ALS ( P  = 4.18e–6). However, the odds of having nail mercury levels above the 90th percentile were 2.3-fold higher among ALS patients compared with controls (odds ratio (OR) = 2.3, 95% confidence interval 1.10–4.58, adjusted for age and smoking status). Conclusion : This finding suggests that excessive mercury exposure may be associated with the neurodegenerative health of aging populations.